2008
DOI: 10.1007/s11859-008-0317-8
|View full text |Cite
|
Sign up to set email alerts
|

Selection of judging indicators for surface morphology of soil crack under different development degrees in Yuanmou arid-hot valley region

Abstract: Quantification of complicated surface morphology of soil crack is a prerequisite and key to soil crack study. This paper takes soil crack quads in Yuanmou arid-hot valley region as examples, selecting several morphological indicators, and analyzes the soil crack's morphological features under various development degrees. By statistic analysis, three quantitative indicators for surface morphology are selected, namely soil crack area density, area weighted mean fractal dimension and connectivity index R, which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The photographs of soil cracks taken in the simulation experiment were processed through the procedures described above, and then the indicators for surface morphology of soil cracks were selected. According to previous research results [5], soil cracks' morphology can be described by three criteria: cracks' morphological intensity, complexity and connectivity. Among them, intensity indicators for surface morphology of cracks are the most visual, precise indicators in expressing crack morphology, which have been applied by several researchers for several times before [6, 7 and 8].…”
Section: Quantitative Analysismentioning
confidence: 95%
“…The photographs of soil cracks taken in the simulation experiment were processed through the procedures described above, and then the indicators for surface morphology of soil cracks were selected. According to previous research results [5], soil cracks' morphology can be described by three criteria: cracks' morphological intensity, complexity and connectivity. Among them, intensity indicators for surface morphology of cracks are the most visual, precise indicators in expressing crack morphology, which have been applied by several researchers for several times before [6, 7 and 8].…”
Section: Quantitative Analysismentioning
confidence: 95%
“…For the measurement of crack characteristics, early researches focused on manually measuring cracks in the field (Novak, 1999;Ringrose-voase and Sanidad, 1996); with the development of computers, image-processing technology has become increasingly advantageous in extracting crack characteristics because of its rapid, accurate and non-destructive detection. Velde (1999) evaluated the fractal dimension of surface crack patterns in various types of soils using box counting method and found that cultivated soils showed the greatest irregularity for a given porosity; Vogel et al (2005) measured the angle distribution of a crack network and used it to identify the blocks segmented by cracks; Xiong et al (2008) extracted the connectivity index to express the development intensity of soil cracks and describe the morphological complexity of crack patterns quantitatively; Liu et al (2013) developed special software CIAS to extract the geometric characteristics of crack patterns such as crack area, crack length, crack width and crack direction automatically, the software showed a great potential to study the generation and development of soil crack patterns. Although it is known as a very common characteristic to distinguish the surface patterns of objects, the texture feature, however, has never been used to describe the extent of soil cracking.…”
Section: Introductionmentioning
confidence: 99%
“…Adrian et al (2000) stated that soil cracks cause worsening in soil water quality and persuade several significant physical, chemical, and biochemical processes in the soil (Yoshida et al 2004). Studying soil cracks has significant importance in understanding the soil degradation processes and subversive pollution of water and the expansion of re-vegetation practices (Xiong et al 2008). Chertkov (2000) affirmed that crack networks in the soil directly depend upon the hydraulic properties of soil.…”
Section: Introductionmentioning
confidence: 99%
“…However, crack area density and length density determines the connectivity of crack 0 s network (Vogel et al 2005). Xiong et al (2008Xiong et al ( , 2009 studied crack length, width and other morphological characteristics to understand the connectivity and complexity of the soil cracks. Tang et al (2010) established that desiccation cracking patterns crack development through moisture content, stiffness and tensile strength of soil, and base adhesion.…”
Section: Introductionmentioning
confidence: 99%